Position of Civil Crime as a Transnational Crime - Muhammad Hatta; Dianti Novita Marwa; Lisa Lestari; Lena Mahara Simahate; Herika Novita; Abdul Azis (International Journal of Law, Crime and Justice, 2025)
Cybercrime is an unlawful act committed using the internet based on sophisticated computer technology, networks and other information technologies. This crime not only affects individuals, but also financial institutions, critical infrastructure, and even national and international security. Cybercrime has characteristics that distinguish it from conventional forms of crime, namely the ability to cross geographical boundaries of countries without physical barriers so that in this case this cybercrime is referred to as transnational crime. The purpose of this study is to examine and analyze the position of cybercrime in the perspective of international law and to examine and analyze the position of cybercrime in the perspective of national law. The results of the study were obtained from the perspective of international law, cybercrime has a strategic position as a global threat that requires a cross-country legal approach. Meanwhile, from the perspective of national law, cybercrime has a central position in the reform of the Indonesian criminal law system. Through the formation and improvement of the ITE Law, as well as increasing the capacity of law enforcement and the community, the state seeks to create a safe, fair and responsible digital space